Proposing immersive virtual reality scenarios for validating verbal content analysis methods in adult samples - Iffland, Judith A.; Volz, Theres; Gubi-Kelm, Silvia (Frontiers in Psychology, 2024)
Verbal content analyses to differentiate truthful and fabricated statements, such as the Criteria-Based Content Analysis (CBCA), are used in lie detection research as well as in practice to assess the credibility of statements in criminal court proceedings. Meta-analyses demonstrate validity of verbal content analyses above chance, but the traditional research paradigms usually lack either ecological or internal validity. The authors suggest the usage of immersive virtual reality scenarios to solve this dilemma, as both types of validity can be increased by this approach, and discuss novel ethical challenges involved. Overall, we argue in favor of using virtual reality scenarios to validate methods for verbal content analysis, but also urge to consider ethical limitations regarding unwanted short- and long-term aftereffects.